2020
DOI: 10.1021/acsaem.9b01441
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mismatching of CuInSe2 and Ni3Al Demonstrates Selective Photoelectrochemical CO2 Reduction to Methanol

Abstract: Photoelectrochemical catalysts are often plagued by ineffective interfacial charge transfer or nonideal optical conversion properties. To overcome this challenge, strategically pairing a catalytically inactive, optically proficient semiconductor with a selective electrocatalyst, coined “catalytic mismatching”, is suggested. Here, chalcopyrite semiconductor CuInSe2 is paired with the electrocatalyst Ni3Al to selectively reduce CO2. This catalytically mismatched system produces methanol at a Faradaic efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Given this finding, it is not quite as surprising that different product yields are observed using a Ni 3 Al catalyst distributed on glassy carbon versus a CIGS (copper, indium, gallium, selenium) based ptype photoelectrode. 10,12,13 In contrast to the above approach, we have also explored the chemistry involved in the homogeneous electroreduction of CO 2 . Presently, our main vehicle for doing this is complexes based on a MnXbpy(CO) 3 motif, which is highly selective for the conversion of CO 2 to CO.…”
Section: Heterogeneous Carbon Dioxide Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this finding, it is not quite as surprising that different product yields are observed using a Ni 3 Al catalyst distributed on glassy carbon versus a CIGS (copper, indium, gallium, selenium) based ptype photoelectrode. 10,12,13 In contrast to the above approach, we have also explored the chemistry involved in the homogeneous electroreduction of CO 2 . Presently, our main vehicle for doing this is complexes based on a MnXbpy(CO) 3 motif, which is highly selective for the conversion of CO 2 to CO.…”
Section: Heterogeneous Carbon Dioxide Reductionmentioning
confidence: 99%
“…It is hypothesized that C–C coupling is possible because the high surface area of the Ni 3 Ga promoted by the HOPG allows surface-bound intermediates to be in close proximity. Given this finding, it is not quite as surprising that different product yields are observed using a Ni 3 Al catalyst distributed on glassy carbon versus a CIGS (copper, indium, gallium, selenium) based p-type photoelectrode. ,, …”
Section: Heterogeneous Carbon Dioxide Reductionmentioning
confidence: 99%
“…Hence, the generation of CH 3 OH in aqueous PEC CRR cells is challenging due to the lack of cocatalysts for CH 3 OH production. [78][79][80][81][82] Several works on the TiO 2 -protected InP and GaP photocathodes have indicated that the oxygen vacancy-rich TiO 2 was active to catalyze the CO 2 reduction to produce CH 3 OH. Further studies on these photocathodes indicated that the oxygen vacancies (Ti 3+ position) were possible active sites for CO 2 -to-CH 3 OH conversion.…”
Section: Pec Co 2 Reduction To Ch 3 Ohmentioning
confidence: 99%
“…Hence, the generation of CH 3 OH in aqueous PEC CRR cells is challenging due to the lack of cocatalysts for CH 3 OH production. [ 78–82 ]…”
Section: Pec Co2 Reduction To Different Productsmentioning
confidence: 99%
“…[157] Aside from those heterojunction catalysts based on p-Si and g-C 3 N 4 , the idea to overcome ineffective interfacial charge transfer or non-ideal optical conversion drives the research towards other not so usual junctions. The literature reports several heterocatalysts free of oxides for photochemical reactions such as MoSe 2 /ZnIn 2 S 4 , [160] black phosphorus and g-C 3 N 4 (BP/g-C 3 N 4 ), [161,162] FeCoS 2 -CoS 2 , [46] CuInSe 2 /Ni 3 Al, [163] and Au/p-GaN. [164] However, until this moment, most of those catalysts were not applied for CO 2 reduction using the PEC technique.…”
Section: Heterojunction Of Different 2d Photoelectrodesmentioning
confidence: 99%